2013
DOI: 10.1155/2013/454209
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Formation in a Diffusive Ratio-Dependent Holling-Tanner Predator-Prey Model with Smith Growth

Abstract: The spatiotemporal dynamics of a diffusive ratio-dependent Holling-Tanner predator-prey model with Smith growth subject to zero-flux boundary condition are investigated analytically and numerically. The asymptotic stability of the positive equilibrium and the existence of Hopf bifurcation around the positive equilibrium are shown; the conditions of Turing instability are obtained. And with the help of numerical simulations, it is found that the model exhibits complex pattern replication: stripes, spots-stripes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Numerous laboratory experiment, and observations have shown that a more suitable general predator-prey system should be based on the "ratio-dependent" theory, especially when predators have to search, share, or compete for food [1][2][3]. And ratiodependent predator-prey systems have been investigated by many scholars [4][5][6][7][8][9][10][11]. In [4], Zhang and Lu considered the following semi-ratio-dependent predator-prey system with the nonmonotonic functional response…”
Section: Introductionmentioning
confidence: 99%
“…Numerous laboratory experiment, and observations have shown that a more suitable general predator-prey system should be based on the "ratio-dependent" theory, especially when predators have to search, share, or compete for food [1][2][3]. And ratiodependent predator-prey systems have been investigated by many scholars [4][5][6][7][8][9][10][11]. In [4], Zhang and Lu considered the following semi-ratio-dependent predator-prey system with the nonmonotonic functional response…”
Section: Introductionmentioning
confidence: 99%